Therapeutic hypothermia after out of hospital cardiac arrest improve 1-year survival rate for selective patients. - Ofir Koren; Ehud Rozner; Sawsan Yosefia; Yoav Turgeman (PLoS ONE, 2020)
Background Therapeutic Hypothermia (TH) is a standard of care after out-of-hospital cardiac arrest (OHCA). Previous reports failed to prove a significant benefit for survival or neurological outcomes. We examined whether the proper selection of patients would enhance treatment efficacy. Method We conducted a retrospective cohort study. Data was collected from January 2000 and August 2018. Patients were enrolled after OHCA and classified into two groups, patients treated with TH and patients who were not treated with TH. Results A total of 92 patients were included in the study. 57 (63%) patients were in the TH Group and 34 (37%) in the Non-TH group. There was no statistical difference in favorable neurological outcomes between the groups. Patients presenting with ventricular fibrillation had a higher 1-year survival rate from TH, while patients with asystole were found to benefit only if they were younger than 65 years (p < .007, p < .02, respectively). Conclusion Therapeutic Hypothermia patients failed to demonstrate a significant benefit in terms of improved neurological outcomes. Patients treated with TH following ventricular fibrillation experienced the most benefit in terms of 1-year survival, while patients who had suffered from asystole experienced a modest benefit only if they were younger than 65 years of age. Guidelines should address age and primary arrhythmia for proper treatment selection.